Seasonal Cycle of the Coastal West Greenland Current System Between Cape Farewell and Cape Desolation From a Very High‐Resolution Numerical Model. Issue 5 (13th May 2021) - Gou, Ruijian; Feucher, Charlène; Pennelly, Clark; Myers, Paul G.
Abstract: The shelf based West Greenland Current System carries both Arctic Water and Greenland meltwater around Cape Farewell, the southern tip of Greenland, where it may impact the deep water formation in the Labrador Sea. Nevertheless, this current system remains largely unknown due to limited observations. Using a very high‐resolution (1°/60°) numerical simulation integrated from 2005 to 2014, the annual cycle of the current structure in the vicinity of southern Greenland is analyzed to present the seasonal variability of the West Greenland Current System. A distinct shelf break West Greenland Coastal Current (WGCC) exists for about half the year between Cape Farewell and Cape Desolation, although it merges with the main jet of the West Greenland Current (WGC) in winter and separates in summer. The WGC has three components at Juliannehaab Bight: A shelf component, a shelf‐break component and a main slope jet. The shelf system is most energetic in fall, when the freshwater transport is also the greatest in a range of 25–40 mSv, with a broad transport minimum in spring in a range of 15–25 mSv. The seasonal cycle is strongest near Cape Farewell and weakest at Cape Desolation. The strength of the shelf system decreases as one moves north as water is lost offshore, with strongest transports of 0.61 Sv to the east of Cape Farewell and weakest of 0.41 Sv at Cape Desolation. This decrease in transport between Cape Farewell and Cape Desolation suggests substantial exchange between WGCC and WGC in this region. Plain Language Summary: A West Greenland Coastal Current (WGCC), located along the west Greenland continental shelf, was previously found to transport cold, fresh water to the Labrador Sea through exchange with the shelf break current, potentially influencing the deep convection that feeds the climate‐related Atlantic Meridional Overturning Circulation. Our very high‐resolution regional model is the first to successfully simulate the WGCC, which is difficult due to its very narrow nature. It is shown that the part of the WGCC that rounds the southern tip of Greenland merges with shelf break current in winter, and the WGCC remains separate from the shelf break current in summer. The main WGCC consists of persistent flow on the shelf except when it splits into multiple branches at Juliannehaab Bight. The WGCC significantly strengthens in summer and autumn. Its volume and freshwater transports increase from a minimum in spring to a maximum in October and this cycle weakens northward and westward along the shelf. The decrease in the transport suggests substantial exchange of WGCC water with the West Greenland Current. Key Points: A shelf break West Greenland Coastal Current exists about half a year between Cape Farewell and Cape Desolation, with a three current system at the Overturning in the Subpolar North Atlantic Program (OSNAP) West section The shelf system is strongest in fall, with largest freshwater transport (25–40 mSv), with a transport minimum in spring (15–25 mSv) The transport decreases as water is lost offshore, decreasing from OSNAP East (0.61 Sv) to Cape Desolation (0.41 Sv)